2012
DOI: 10.1097/eja.0b013e32834fc260
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil for labour analgesia

Abstract: During labour, remifentanil-PCA provided superior analgesia and higher patient satisfaction compared with pethidine with a comparable degree of adverse events. Epidural analgesia provided superior pain relief in comparison with remifentanil. Due to a low number of reported adverse events, the safety issue of remifentanil use in labour remains an open question that needs to be addressed in future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(19 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…The cumulative evidence suggests that compared with pethidine, its use for labour analgesia is associated with significantly improved pain relief and satisfaction and is associated with a significantly decreased conversion rate to epidural analgesia [30]. Trials comparing intravenous patient controlled analgesia using remifentanil with epidural analgesia suggest – which is not a surprise – a more pronounced reduction in pain scores with neuraxial analgesia [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative evidence suggests that compared with pethidine, its use for labour analgesia is associated with significantly improved pain relief and satisfaction and is associated with a significantly decreased conversion rate to epidural analgesia [30]. Trials comparing intravenous patient controlled analgesia using remifentanil with epidural analgesia suggest – which is not a surprise – a more pronounced reduction in pain scores with neuraxial analgesia [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Trials comparing intravenous patient controlled analgesia using remifentanil with epidural analgesia suggest – which is not a surprise – a more pronounced reduction in pain scores with neuraxial analgesia [30,31]. When it comes to overall satisfaction with the analgesic technique, however, the studies report that “Maternal satisfaction was similar” [31] or “Patient satisfaction scores during and after delivery were similar in both groups” [32].…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl was avoided to prevent further pulmonary compromise in the premature fetus, and since other options were available and deemed safe for both the mother and fetus, those were utilized, rather than performing a cardiac induction with high dose opioids. However, another option that has been shown to be efficacious and safe for both a cardiac parturient and her fetus is the use of Remifentanil, which has been used as a low dose patient-controlled analgesia (PCA) infusion for many laboring women who cannot have neuraxial analgesia during labor [18][19][20][21][22][23] . Short-acting opioid infusions have been proven to be safe for the patient, with minimal effects on the fetus, supposing the parturient can tolerate the hemodynamic effects of such an anesthetic approach [3] .…”
Section: Discussionmentioning
confidence: 99%
“…[5] Their study found that the mean pain scores measured with the visual analog scale (VAS) ranged from 4.6 to 8.5 of the maximum of 10. [5] Although previous studies have used neuraxial analgesia for ECV, [10,11,12] which has been associated with improved pain scores and increased success of ECV, those drugs may also be associated with maternal hypotension, sedation, and other adverse events (AEs). [13,14] Cluver and colleagues conducted a Cochrane systematic review and found that use of regional analgesia did not produce a corresponding decrease in the cesarean rate, [6] although it can increase the success rate of ECV.…”
Section: Introductionmentioning
confidence: 99%